A simultaneous optimization model for a heat-integrated syngas-to-methanol process with Kalina Cycle for waste heat recovery. (15th July 2021) - Zhuang, Yu; Zhou, Congcong; Zhang, Lei; Liu, Linlin; Du, Jian; Shen, Shengqiang
Abstract: The syngas to methanol (STM) process is an energy-intensive chemical production process, and effective utilization of waste heat can improve energy and economy efficiency. To address current challenges that complex interactions between process synthesis and waste heat recovery are not considered, a novel simultaneous optimization model is proposed for a heat-integrated syngas-to-methanol process with Kalina Cycle (KC) for waste heat recovery, where the identified key parameters of KC and STM are optimized simultaneously without reducing the overall conversion of hydrogen to produce methanol. In developing the model, an enhanced Heat Integration model that considers variable temperatures and flowrates is established to perform thermal cycle optimization with process synthesis by combination of simulation-based modelling approach and equation-based mathematical programming approach. The STM process is synthesized based on a rigorous kinetic modelling approach and the effect of process parameters on waste heat recovery is further analyzed by control variable method. The results show that the net power output of the whole system increases with the decrease of reaction pressure. The optimal medium temperature and inlet temperature of reactor are 180 °C and 160 °C, respectively. Moreover, the presented model can achieve the optimal coupling structure of KC and STM process with the maximized net power output of 15, 206.3 kW, which increases by 81.6% compared with that of 8371.4 kW derived by the traditional sequential optimization method in previous study. Graphical abstract: Image 1 Highlights: The syngas to methanol process is coupled with KC for waste heat recovery. The interactions between process synthesis and waste heat recovery are considered. A simultaneous optimization model for STM process with KC is proposed. The variable heat capacities of streams in the integrated system are considered. The optimal coupling structure with net power output of 15206.3 kW is obtained.